Fetal Outcome in Primigravida Females Presenting with Breech Pregnancy at Term - Jamali, Kainat; Naz, Shabnam; Shaikh, Afsheen Shahid; Shaikh, Fozia; Paras; Jokhio, Shazmina (Indus Journal of Bioscience Research, 2025)
Introduction: Breech presentation, defined as the fetus being positioned with its buttocks or feet closest to the birth canal instead of the cephalic position, is a significant clinical concern, especially at term. Objective: The main objective of the study is to find the fetal outcome in primigravida females presenting with breech pregnancy at term. Methodology: This descriptive cross-sectional study was conducted in the Department of Obstetrics & Gynecology, Shaikh Zaid Women Hospital, Larkana, a tertiary care hospital from  September, 2024 to May, 2025 providing comprehensive maternal and neonatal healthcare services. A detailed obstetric history and examination were performed, and findings were documented. The breech presentation was confirmed using ultrasonography. Results: The study included 100 primigravida females presenting with breech pregnancy at term. The mean age of the participants was 25.4 ± 3.2 years, with the majority (62%) aged between 20-30 years. The mean gestational age at delivery was 38.6 ± 1.1 weeks. Breech presentations were categorized as Frank Breech in 70% of cases and Complete Breech in 30%. Regarding delivery modes, 72% underwent cesarean sections, while 28% had vaginal breech deliveries. Poor Apgar scores (